Fungsi Supervisi Akademik Pengawas terhadap Kepemimpinan Kepala MIN 1 Aceh Timur - Amri, Yusnil; Buto, Zulfikar Ali; Mawiyah, Aisyah (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
This research is motivated by the fact that coordination between supervisors and school principals in providing guidance to teachers at MIN 1 East Aceh has not occurred effectively. The problem formulation is the planning of the supervisor's academic supervision towards the leadership of the Madrasah Head, the implementation of academic supervision carried out by the supervisor in improving the leadership of the madrasah head as a learning leader, and the function of the supervisor's academic supervision towards the leadership of the Madrasah Head at MIN 1 East Aceh. The aim of this research is to describe the function of the supervisor's academic supervision of the leadership of the Madrasah Head at MIN 1 East Aceh. This research uses a descriptive method with a qualitative approach. Data was collected by observation, interviews and documentation. Several findings that show the function of academic supervision of school supervisors on the leadership of the Madrasah Head in MIN 1 East Aceh include Strengthening Learning Planning, Strengthening Presentation of Material, Strengthening Learning Evaluation, Strengthening Class Management, Strengthening Teaching Material, Strengthening Understanding of the Curriculum and Strengthening Group Collaboration.